Composite viscosity reducer, preparation method and application thereof, and method for responsively demulsifying thick oil produced liquid
By modifying the composite viscosity reducing agent of graphene oxide and cyclodextrin-based surfactant, the problems of poor viscosity reduction and difficulty in demulsification of heavy oils are solved, and the efficient emulsification of heavy oils is achieved and the CO2 responsive emulsification of heavy oils is simplified to post-treatment of the production liquid, and the stability and carrying efficiency of nanomaterials are significantly improved.
Patent Information
- Application Number
- CN202311106896.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-30
AI Technical Summary
The prior art has problems such as poor emulsification and difficulty in demulsification in the process of heavy oil emulsification and viscosity reduction, and the stability of nanomaterials in formation water and adsorption loss on rock surfaces need to be solved urgently.
By grafting the graphene oxide by polyethylene glycol monoglycidyl ether, a modified graphene oxide nanomaterial was obtained and combined with a cyclodextrin-based surfactant to form a composite viscosity reducing agent. The interfacial activity of the modified graphene oxide and the inclusion and loading of cyclodextrin can be used to achieve emulsification and viscosity reduction of the heavy oil, and the post-treatment of the production liquid is simplified by CO2-responsive deemulsification.
It significantly improves the emulsification and viscosity reduction effect of heavy oil, reduces the adsorption loss of nanomaterials, realizes easy treatment of heavy oil production liquid, and solves the stability problem of traditional nanomaterials in high-salt environments.
Smart Images

Figure CN119529802A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heavy oil emulsification and viscosity reduction production, and in particular to a composite viscosity reducer and a preparation method and application thereof, and a method for responsive demulsification of heavy oil produced fluid. Background Art
[0002] As crude oil production enters the middle and late stages, the reserves of low-viscosity crude oil decrease, while the development proportion of high-viscosity heavy oil increases year by year. Compared with low-viscosity crude oil, heavy oil contains more colloids and asphaltene, has high viscosity and poor fluidity, which greatly increases the difficulty of its production.
[0003] Nanomaterials are a commonly used oilfield additive, which has the characteristics of high temperature resistance, high pressure, high salt and shear resistance, and complements traditional organic chemicals. 2 Spherical inorganic nanomaterials represented by graphene oxide and its modified products have defects such as large dosage and unsatisfactory oil displacement effect. Recent basic research has found that the nano-scale sheet structure of graphene oxide gives the material a higher theoretical specific surface area and specific surface energy, making its adsorption efficiency at the oil / water interface extremely high, and it can emulsify Daqing crude oil at the ppm level (Energy & Fuels, 2017, 31, 13439.).
[0004] In addition, CN114058342A discloses a modified graphene oxide nanosheet thickener, which can control the interaction between polymer molecules by grafting small molecule surfactants onto graphene oxide, thereby improving the viscosity enhancement efficiency of the polymer. However, the heavy oil viscosity reduction mining process requires reducing the viscosity of the crude oil system, and the thickener modified graphene oxide nanomaterial is obviously not suitable for this field.
[0005] Theoretically, the single-layer structure of graphene oxide enables it to spontaneously adsorb efficiently at the oil-water interface to form a "rigid" interface film. This "rigid" interface film is more stable than the "flexible" interface film formed by the adsorption of traditional surfactants at the interface, but it is difficult to meet the interface curvature required for the formation of oil-in-water emulsions. At the same time, although some Janus nanomaterials can form Pickering emulsions after emulsifying oily components, this type of emulsion is very stable and difficult to demulsify, making it difficult to post-process crude oil produced fluids and unable to be refined and utilized. At the same time, due to the large specific surface area of nanomaterials, their stability in formation water and adsorption loss on the rock surface also need to be solved urgently.
[0006] Cyclodextrin (CDs), which is composed of multiple D-pyranose glucose units connected by α-1,4 glycosidic bonds, has a truncated cone structure and is a typical functional host molecule. It can form complexes with a variety of active molecules through the inclusion complex of the cavity, and has the advantages of being green and easy to degrade. It is widely used as an ideal carrier for drug molecules and nanomaterials. However, the steric hindrance of cyclodextrin itself is large and cannot play the role of emulsification and viscosity reduction.
[0007] Therefore, it is urgent to develop a new composite emulsification and viscosity reduction system to improve the carrying effect of graphene oxide-based nanomaterials, enhance their emulsification and viscosity reduction effect on heavy oil, and at the same time achieve stimulus-responsive demulsification of oil-water mixed emulsions, so that the produced fluid can be easily post-processed. Summary of the invention
[0008] The purpose of the present invention is to overcome the problems of poor emulsification viscosity reduction effect and great difficulty in demulsification in the prior art.
[0009] During the research process, the inventors found that the modified graphene oxide nanomaterial obtained by grafting and modifying graphene oxide with polyethylene glycol monoglycidyl ether has better salt resistance and can be stably dispersed in formation water. At the same time, the modified graphene oxide nanomaterial has excellent interfacial activity and synergistic emulsification and viscosity reduction performance. The modified graphene oxide, water and cyclodextrin-based surfactants are used to form an active composite viscosity reducer. The cyclodextrin-based surfactant in the composite viscosity reducer can encapsulate and stabilize the modified graphene oxide material, so that it is selectively released when it encounters oil, and forms a stable oil-water interface film with the colloid in the heavy oil under the host-guest synergistic effect and co-adsorption at the oil-water interface, ultimately achieving the goal of emulsifying and reducing the viscosity of the heavy oil. At the same time, the pH responsive sites of the composite viscosity reduction system are used to realize the CO 2 reduction of the emulsion system. 2 Responsive demulsification makes the produced fluid easy to post-process.
[0010] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite viscosity reducer, which contains the following components which are stored independently or two or more components are stored as a mixture: a cyclodextrin-based surfactant, water, and modified graphene oxide;
[0011] The modified graphene oxide comprises graphene oxide and grafted polyoxyethylene chains, wherein the chemical formula of the polyoxyethylene chains is -CH 2 CH(OH)CH 2 O(CH 2 CH 2 O) n CH 2 CH 2 OH, wherein n is selected from any integer from 3 to 20;
[0012] The cyclodextrin-based surfactant contains -OSO 3Na, -OH groups;
[0013] The mass ratio of the modified graphene oxide to the cyclodextrin-based surfactant is 1:(10-500).
[0014] The second aspect of the present invention provides a method for preparing the composite viscosity reducer described in the first aspect, the method comprising: contacting a cyclodextrin-based surfactant, modified graphene oxide and water.
[0015] The third aspect of the present invention provides the use of the composite viscosity reducer described in the first aspect in the field of heavy oil production.
[0016] A fourth aspect of the present invention provides a method for responsive demulsification of heavy oil produced fluid, the method comprising:
[0017] (1) bringing the composite viscosity reducer described in the first aspect into first contact with heavy oil to obtain an oil-water mixed emulsion;
[0018] (2) introducing CO into the oil-water mixed emulsion 2 , so that the oil-water mixed emulsion can responsively break up the emulsion and separate the water.
[0019] The modified graphene oxide provided by the present invention has excellent salt resistance and synergistic emulsification and viscosity reduction performance. When it is used in a composite viscosity reducer with a cyclodextrin-based surfactant, the viscosity reduction effect of the viscosity reducer on heavy oil can be significantly improved.
[0020] The composite viscosity reducer provided by the present invention has the properties of two types of active materials, cyclodextrin-based surfactant and modified graphene oxide. Through the host-guest interaction and synergistic adsorption between the components, a stable oil-water interface film is formed, thereby achieving emulsification and viscosity reduction of extra-heavy oil. At the same time, the pH responsive sites of the composite viscosity reducer are utilized. When CO is introduced, 2 After that, the oil-water mixed emulsion can be quickly demulsified and separated from the water, making the post-processing of crude oil simple.
[0021] In addition, the present invention utilizes the encapsulation effect of cyclodextrin-based surfactants on modified graphene oxide nanomaterials, and can also achieve targeted release of modified graphene oxide nanomaterials when encountering oil, thereby reducing the adsorption loss of nanomaterials on the rock surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the mass spectrum of polyethylene glycol monoglycidyl ether prepared in Preparation Example 1 of the present invention.
[0023] Figure 2 This is the infrared spectrum of the modified graphene oxide in Preparation Example 1 of the present invention.
[0024] Figure 3 This is the mass spectrum of the cyclodextrin-based surfactant intermediate in Preparation Example 2 of the present invention.
[0025] Figure 4 is the cyclodextrin-based surfactant in Preparation Example 2 of the present invention 1 H NMR spectrum.
[0026] Figure 5 This is the UV-visible spectrum of the modified graphene oxide aqueous dispersion prepared in Preparation Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] As mentioned above, the first aspect of the present application provides a composite viscosity reducer, which contains the following components stored independently or in a mixture of two or more: a cyclodextrin-based surfactant, water, and modified graphene oxide;
[0029] The modified graphene oxide comprises graphene oxide and grafted polyoxyethylene chains, wherein the chemical formula of the polyoxyethylene chains is -CH 2 CH(OH)CH 2 O(CH 2 CH 2 O) n CH 2 CH 2 OH, wherein n is selected from any integer from 3 to 20;
[0030] The cyclodextrin-based surfactant contains -OSO 3 Na, -OH groups;
[0031] The mass ratio of the modified graphene oxide to the cyclodextrin-based surfactant is 1:(10-500).
[0032] In the present invention, n in the polyoxyethylene chain is any integer of 3-20, for example, n is 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, and any range between any two values, preferably any integer of 5 to 15. The inventors have found that in this preferred case, the modified graphene oxide has better salt resistance and interface properties, and can be used in the composite viscosity reducer to obtain a better viscosity reduction effect.
[0033] Preferably, the mass ratio of the modified graphene oxide to the cyclodextrin-based surfactant is 1:(15-200). The inventors found that in this preferred case, the obtained composite viscosity reducer has a more excellent viscosity reducing effect.
[0034] Preferably, the grafting rate of the polyethylene oxide chain in the modified graphene oxide is 30-50%, preferably 35-46%; more preferably 40-46%. In this preferred case, the inventors of the present invention found that the obtained modified graphene oxide has more excellent synergistic emulsification viscosity reduction performance and salt resistance, and can be stably dispersed in high-salt formation water without agglomeration and precipitation. Using it in a viscosity reducer can better improve the stability of the oil-water interface film and the emulsification viscosity reduction effect.
[0035] In the present invention, the grafting rate of the polyoxyethylene chain is calculated based on the difference in mass loss rate of the two graphene oxide materials before and after grafting modification after heating at 800°C, that is, grafting rate = {(m[modified material]-m[modified material after heating at 800°C]) / m[modified material]-(m[graphene oxide]-m[graphene oxide after heating at 800°C]) / m[graphene oxide]}*100%.
[0036] In the present invention, the connecting group between the obtained graphene oxide and the polyoxyethylene is an ether bond, which is more stable than an ester bond and can withstand acid / alkali aqueous solutions; at the same time, the terminal of the obtained modified graphene oxide is a hydroxyl group and will no longer participate in the grafting reaction.
[0037] Preferably, the modified graphene oxide in the present invention does not contain organic amine.
[0038] In the present invention, the infrared spectrum test instrument is a NICOLET 6700 infrared spectrometer, and the test range is 450-4000cm -1 The results are the data after deducting the air background.
[0039] Preferably, the modified graphene oxide is obtained by dialyzing a modified graphene oxide aqueous dispersion.
[0040] Preferably, in the composite viscosity reducing agent, the modified graphene oxide is added in the form of a modified graphene oxide aqueous dispersion.
[0041] In order to further improve the salt resistance and synergistic emulsification and viscosity reduction performance of modified graphene oxide, the present invention provides a preferred implementation mode, wherein the modified graphene oxide aqueous dispersion is prepared by a method comprising the following steps:
[0042] S1: Under alkaline conditions, the graphene oxide aqueous dispersion is activated with β-cyclodextrin to obtain an activation solution;
[0043] S2: performing a grafting reaction on the activation solution and polyethylene glycol monoglycidyl ether to obtain a grafted product;
[0044] S3: using an acid to adjust the pH value of the grafted product to neutral, and then adding amylase to wash it to obtain the modified graphene oxide aqueous dispersion.
[0045] Preferably, the sheet diameter of the graphene oxide is no more than 2 μm, preferably 50-500 nm. In this preferred case, the inventors of the present invention found that the obtained modified graphene oxide has better salt resistance.
[0046] Preferably, the raw material of the graphene oxide is microcrystalline graphite and / or flake graphite. In the present invention, the microcrystalline graphene oxide prepared by microcrystalline graphite can be stably dispersed in high-salinity formation water, and the dispersion stability of the material has strong tolerance to acid / alkali, and the interfacial tension is reduced by one order of magnitude compared with that before modification, so it is suitable for use in conjunction with different acid / alkaline flooding systems. At the same time, the cost of using microcrystalline graphite as a raw material is lower than that of flake graphite, making the modified graphene oxide more economical in application.
[0047] Preferably, in step S1, the activation reaction conditions include: reaction temperature of 60-100°C, preferably 70-90°C; reaction time of 1-4h, preferably 2-3h. The inventors found that carrying out the activation reaction under such conditions is conducive to improving the hydroxyl activity in the activation reaction and further improving the grafting efficiency of the polyoxyethylene chain.
[0048] In the present invention, the activation reaction is carried out under stirring conditions, and the stirring rate of the activation reaction is 200-800 rpm, preferably 300-500 rpm.
[0049] Preferably, in step S2, the grafting reaction conditions include: reaction temperature of 60-100°C, preferably 70-90°C; reaction time of 4-16h, preferably 6-12h.
[0050] Preferably, in step S3, the washing time is 1-4h, preferably 2-3h. In the present invention, the washing is carried out under stirring conditions, and there is no particular limitation on the washing stirring rate. Those skilled in the art can make adaptive adjustments as needed. Preferably, the washing stirring rate is 200-800rpm, preferably 300-500rpm.
[0051] Preferably, in step S1, the concentration of graphene oxide in the graphene oxide aqueous dispersion is greater than 20 mg / L, preferably 500-2000 mg / L.
[0052] Preferably, the amount of β-cyclodextrin is 100-800 mg, preferably 300-500 mg, based on the total volume of the mixed solution of graphene oxide aqueous dispersion and cyclodextrin being 1 L. In the present invention, if the mass concentration of cyclodextrin is too low, the grafting effect is poor and the grafting rate is low; if the mass concentration of cyclodextrin is too high, it will cause a waste of raw materials.
[0053] Preferably, the alkaline condition in step S1 is provided by an alkaline substance, and the alkaline substance is sodium hydroxide and / or potassium hydroxide. In the present invention, the activation reaction is carried out under alkaline conditions, which can increase the activity of hydroxyl groups in the activation solution and increase the grafting rate of polyoxyethylene chains in the modified graphene oxide.
[0054] Preferably, in step S1, the pH value of the alkaline condition is 9-12, preferably 10-11.
[0055] Preferably, the mass ratio of polyethylene glycol monoglycidyl ether to graphene oxide is (5-100):1, for example 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, and any range between any two values, preferably (10-30):1.
[0056] Preferably, in step S3, based on the total volume of the graphene oxide aqueous dispersion as 1 L, the amount of the amylase used is 50-800 mg, preferably 100-400 mg.
[0057] Preferably, in step S3, the acid is selected from at least one of hydrochloric acid and sulfuric acid; the concentration of the acid is preferably 0.1-10 mol / L.
[0058] In step S3 of the present invention, amylase is used for washing, and cyclodextrin can be removed by enzymatic hydrolysis.
[0059] According to another preferred embodiment, in step S2, the polyethylene glycol monoglycidyl ether is prepared by the following method:
[0060] Carrying out a first reaction between polyethylene glycol, potassium carbonate and epichlorohydrin under stirring conditions to obtain the polyethylene glycol monoglycidyl ether;
[0061] The molar ratio of the polyethylene glycol, potassium carbonate and epichlorohydrin is 1:(0.1-1):(1.1-10).
[0062] Preferably, the molar ratio of the polyethylene glycol, potassium carbonate and epichlorohydrin is 1:(0.5-1):(1.5-10). The inventors found that in this preferred case, the obtained polyethylene glycol monoglycidyl ether is used to prepare modified graphene oxide, and the obtained modified graphene oxide has better enhanced emulsification and viscosity reduction effect.
[0063] Preferably, the polyethylene glycol monoglycidyl ether has the following structural formula: n is any integer of 3-20, preferably any integer of 5-15.
[0064] Preferably, the temperature of the first reaction is 20-50°C, preferably 25-40°C; the reaction time is 12-36h, preferably 20-30h.
[0065] In the present invention, the first reaction is preferably carried out under stirring conditions. There is no particular limitation on the stirring rate, and those skilled in the art can make adaptive adjustments as needed. Preferably, the stirring rate is 200-800 rpm, preferably 300-500 rpm.
[0066] Preferably, the average molecular weight of the polyethylene glycol is 200-600. In the present invention, if the average molecular weight of the polyethylene glycol is too high, the polyethylene glycol exists in a solid form, and the reaction yield is low; if the average molecular weight of the polyethylene glycol is too low, the obtained polyethylene glycol monoglycidyl ether has insufficient stability.
[0067] Preferably, after the first reaction is completed, solvent extraction and solvent removal are sequentially performed to obtain the polyethylene glycol monoglycidyl ether.
[0068] The present invention has no particular limitation on the extraction method. For example, polyethylene glycol monoglycidyl ether can be extracted into a dichloromethane phase using a water / dichloromethane solvent system with a volume ratio of 1 / 1, the dichloromethane phase is collected, and the solvent is removed to obtain polyethylene glycol monoglycidyl ether.
[0069] It should be noted that in the present invention, the method for preparing the modified graphene oxide is preferably carried out under stirring conditions, and there is no particular requirement for the stirring speed, and the stirring speed can be carried out using parameters known in the art. For example, the stirring speed can be 200-800 rpm, preferably 300-500 rpm.
[0070] The aforementioned preparation method of the present invention may also involve various post-processing operations known in the art, such as rotary evaporation, extraction, washing, filtration, etc. The present invention has no particular limitation on this, and those skilled in the art should not understand it as a limitation on the present invention.
[0071] The preparation method of the modified graphene oxide provided by the present invention is simple, environmentally friendly and easy to operate. The ring-opening reaction between hydroxyl and polyethylene glycol monoglycidyl ether is used to graft hydrophilic polyoxyethylene groups on the surface of graphene oxide. Compared with polyethylene glycol diglycidyl ether, the modification using polyethylene glycol monoglycidyl ether in the present invention can effectively avoid bridging between nanosheets, thereby improving the salt resistance of the modified graphene oxide and effectively inhibiting the accumulation and agglomeration of graphene oxide. Moreover, the addition of β-cyclodextrin can provide hydrophobic reaction sites for the reaction, thereby improving the success rate of grafting polyoxyethylene groups on the surface of graphene oxide.
[0072] Preferably, the cyclodextrin-based surfactant has a structure shown in formula (I):
[0073]
[0074] Wherein, in the structure of formula (I), x is 2, y is any integer selected from 1-5, z is any integer from 0-4, and y+z=5, -C 12 H 25 The inventors found that in this preferred case, the obtained composite viscosity reducer has a better viscosity reducing effect.
[0075] Preferably, the amount of water used is such that in the composite viscosity reducer, the mass concentration of the modified graphene oxide is 10 mg / L-50 mg / L, and the mass concentration of the cyclodextrin-based surfactant is 500 mg / L-5000 mg / L.
[0076] It should be noted that the water in the composite viscosity reducer may be deionized water or formation water with a mineralization of less than 50,000 mg / L, and those skilled in the art may select the water according to their needs.
[0077] It should be noted that, in the present invention, the mass concentration of the modified graphene oxide is calculated based on the mass concentration of graphene oxide.
[0078] More preferably, the amount of water used is such that in the composite viscosity reducer, the mass concentration of the modified graphene oxide is 10 mg / L-30 mg / L, and the mass concentration of the cyclodextrin-based surfactant is 1000 mg / L-2000 mg / L. The inventors have found that in this preferred case, the composite viscosity reducer has a better emulsification viscosity reduction effect and a better demulsification and water separation effect.
[0079] The present invention has no requirements for the preparation method of the cyclodextrin-based surfactant, and those skilled in the art can prepare it by using known technical means in the art. However, in order to obtain a cyclodextrin-based surfactant with better surface activity, the present invention provides a preferred method for preparing the cyclodextrin-based surfactant, which comprises:
[0080] Sa: in the presence of solvent I and a catalyst, β-cyclodextrin and 1,2-epoxytetradecane are subjected to a first contact reaction, and filtered to obtain an intermediate product;
[0081] Sb: in the presence of solvent II, the intermediate product is subjected to a sulfonation reaction with a sulfonating agent to obtain a mixture IV;
[0082] Sc: adjusting the pH value of the mixture I to 7-9 using sodium hydroxide; removing the solvent to obtain the cyclodextrin-based surfactant.
[0083] In the present invention, the method for preparing the cyclodextrin-based surfactant is preferably carried out under stirring. There is no particular requirement for the stirring speed, and the stirring can be carried out using parameters known in the art.
[0084] Preferably, in step Sa, the conditions of the first contact reaction include: temperature of 60-90° C. and time of 3-8 hours.
[0085] Preferably, the conditions of the sulfonation reaction include: temperature of 0-90° C. and time of 1-24 h.
[0086] Preferably, in step Sa, the solvent I is water, and the catalyst is an alkali metal hydroxide or 4-dimethylaminopyridine.
[0087] Preferably, the alkali metal hydroxide is selected from at least one of NaOH and KOH.
[0088] Preferably, in step Sa, relative to 1 mmol of the β-cyclodextrin, the amount of the solvent I is 1-10 mL, and the amount of the catalyst is 0.005-0.1 mmol.
[0089] Preferably, in step Sa, the molar ratio of the β-cyclodextrin to the 1,2-epoxytetradecane is 1:(1-32). More preferably, the molar ratio of the β-cyclodextrin to the 1,2-epoxytetradecane is 1:7.
[0090] According to another preferred embodiment, in step Sb, the mass ratio of the intermediate to the sulfur trioxide pyridine complex is 1:1.0-3.0.
[0091] Preferably, the active SO in the sulfur trioxide pyridine complex 3 The content is 45-55wt%.
[0092] Preferably, relative to 1 g of the intermediate product, the amount of the solvent II is 5-20 mL.
[0093] Preferably, in step Sb, the conditions of the sulfonation reaction at least meet the following conditions: temperature of 0-90° C. and time of 1-24 h.
[0094] Preferably, in step Sb, the solvent II is selected from at least one of tetrahydrofuran, N,N-dimethylformamide and N,N-dimethylacetamide.
[0095] In step Sc of the present invention, the sodium hydroxide is preferably added in the form of an aqueous solution, and the concentration of the aqueous solution of sodium hydroxide is 5wt%-15wt%.
[0096] The composite viscosity reducer provided by the present invention has an excellent emulsification and viscosity reduction effect on heavy oil through the synergistic effect of modified graphene oxide and cyclodextrin-based surfactant.
[0097] As mentioned above, the second aspect of the present invention provides a method for preparing the composite viscosity reducer described in the first aspect, the method comprising: contacting a cyclodextrin-based surfactant, modified graphene oxide and water.
[0098] It should be noted that in the present invention, the definitions and amounts of the cyclodextrin-based surfactant, modified graphene oxide, and water are the same as the definitions and contents of the corresponding components described in the first aspect, and will not be repeated here. Those skilled in the art should not understand this as a limitation to the present invention.
[0099] Preferably, the contacting conditions include: temperature of 10-35°C, time of 30-60 min, and stirring speed of 100-500 rpm.
[0100] As mentioned above, the third aspect of the present invention provides the use of the composite viscosity reducer described in the first aspect in the field of heavy oil production.
[0101] As mentioned above, the fourth aspect of the present invention provides a method for responsive demulsification of heavy oil produced fluid, the method comprising:
[0102] (1) bringing the composite viscosity reducer described in the first aspect into first contact with heavy oil to obtain an oil-water mixed emulsion;
[0103] (2) introducing CO into the oil-water mixed emulsion 2 , so that the oil-water mixed emulsion breaks up and separates the water.
[0104] Preferably, the viscosity of the heavy oil at 50° C. is 10000-30000 mPa·s.
[0105] Preferably, the method further comprises: in step (1), allowing the substance obtained after the first contact to stand for 1-4 hours to obtain an oil-water mixed emulsion.
[0106] Preferably, in step (1), the mass ratio of the composite viscosity reducer to the heavy oil is 3:7 to 7:3. In this preferred embodiment, the inventors found that the composite viscosity reducer has a better emulsification and viscosity reduction effect on the heavy oil, and the viscosity reduction rate of the target heavy oil is not less than 99%.
[0107] Preferably, in step (1), the conditions for the first contact include: temperature of 40-60° C. and time of 10-300 min.
[0108] Preferably, in step (2), CO is introduced 2 The gas flow rate is 0.5-5 L / min, and the ventilation time is 1-5 min. More preferably, in step (2), CO is introduced 2 The air flow rate is 0.5-2L / min, and the ventilation time is 1-5min. In this preferred case, the inventors found that the composite viscosity reducer has a better demulsification effect on the oil-water mixed emulsion containing heavy oil.
[0109] The method for responsive demulsification of produced heavy oil provided by the present invention uses a composite viscosity reducer to emulsify and reduce the viscosity of the heavy oil, and utilizes the pH responsive groups of the cyclodextrin-based surfactant in the composite viscosity reducer to react with CO 2 Responsive, when CO is introduced 2 After demulsification, the emulsion can be quickly demulsified and phase separated, making crude oil post-processing simple.
[0110] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, the reagents used are all commercially available chemical reagents, and there is no particular limitation on this. The water used in the following preparation examples is all distilled water, and the water used in the embodiments and comparative examples is all formation water with a salinity of 20000 mg / L, and the room temperature represents 25±3°C.
[0111] The main raw materials used in the examples are as follows:
[0112] Graphene oxide: single-layer nanomaterial, sheet diameter 50-100 nm, mass concentration 0.5 mg / mL, purchased from Pioneer Nanomaterial Technology Co., Ltd.;
[0113] Epichlorohydrin: purity 99%, purchased from Beijing Yiinuokai Technology Co., Ltd.;
[0114] Polyethylene glycol 400: average molecular weight 400, purchased from Beijing Yiinuokai Technology Co., Ltd.;
[0115] β-cyclodextrin: purity 99%, purchased from Beijing Yiinuokai Technology Co., Ltd.;
[0116] 1,2-Epoxytetradecane: purity 95%, purchased from TCI;
[0117] Amylase: α-amylase, purity 2000u / g, purchased from Adamas Reagent Co., Ltd.
[0118] Preparation Example 1: Preparation of modified graphene oxide
[0119] (1) Take 100 mL of graphene oxide aqueous dispersion (500 mg / L), add 50 mg of β-cyclodextrin, then add sodium hydroxide to adjust the pH value of the system to 10.0, stir at 80° C. and 500 rpm for 2 hours to obtain an activation solution;
[0120] (2) Weigh 16 g of polyethylene glycol 400 and 5.5 g of potassium carbonate in a single-necked bottle, add 10 g of epichlorohydrin under stirring conditions at 25°C, and stir at a rate of 500 rpm. Continue to react for 24 hours and then stop stirring. Use 200 mL of a mixed solvent of water / dichloromethane (volume ratio 1:1) to extract polyethylene glycol monoglycidyl ether into a dichloromethane phase. Collect the dichloromethane phase, remove the solvent, and obtain the product polyethylene glycol monoglycidyl ether;
[0121] Then, 1.5 g of polyethylene glycol monoglycidyl ether was added to the activation solution, and the reaction was continued at 80° C. and 500 rpm for 8 hours. The heating was stopped and the mixture was cooled to room temperature to obtain a grafted product.
[0122] (3) Add 1 mol / L hydrochloric acid to the grafted product to adjust the pH value to 7, then add 10 mg of amylase and stir at 25° C. and 500 rpm for 3 hours to obtain a modified graphene oxide aqueous dispersion.
[0123] The polyethylene glycol monoglycidyl ether obtained in step (2) was subjected to mass spectrometry analysis, and the mass spectrum was as follows: Figure 1 As shown. Since polyethylene glycol 400 is a mixture, its mass spectrum also shows multiple molecular ion peaks accordingly. For example, 449.5 corresponds to the polyethylene glycol monoglycidyl ether product with an n value of 7, 493.5 corresponds to the polyethylene glycol monoglycidyl ether product with an n value of 8, and 537.5 corresponds to the polyethylene glycol monoglycidyl ether product with an n value of 9.
[0124] 10 mL of the modified graphene oxide aqueous dispersion prepared above was dialyzed in distilled water for 1 week through a dialysis membrane to remove unreacted raw materials, and then the dialyzed graphene oxide aqueous dispersion was freeze-dried, and the structure of the modified graphene oxide was characterized by infrared spectroscopy. The infrared spectrum is shown in FIG. Figure 2 shown.
[0125] exist Figure 2 In the spectrum at 3432cm -1The characteristic absorption peaks at 1730cm are the stretching vibration peaks of the remaining unreacted hydroxyl groups in graphene oxide and the newly generated hydroxyl groups after the epoxy groups open. -1 The characteristic absorption peak at 1633 cm -1 The characteristic absorption peak at 1101cm -1 The peak at 845 cm corresponds to the stretching vibration peak of COC in the polyoxyethylene group. -1 The peak at 1450cm is the stretching vibration peak of CC in the polyoxyethylene group. -1 and 2855cm -1 The peak at 40 corresponds to the CH vibration absorption peak of the polyoxyethylene group. The above peaks prove that the polyoxyethylene chain has been connected to the graphene oxide surface through chemical bonds.
[0126] Weigh 0.50 g of freeze-dried modified graphene oxide material powder into a quartz boat, heat it to 800°C at a heating rate of 10°C / min in a tube furnace and keep it at a constant temperature for 2 h. The mass loss was measured, and the grafting rate of polyoxyethylene groups on the surface of graphene oxide was calculated to be 45.2% according to the above-mentioned grafting rate formula.
[0127] Preparation Example 2: Preparation of cyclodextrin-based surfactant
[0128]
[0129] 10 mmol of β-cyclodextrin and 70 mmol of 1,2-epoxytetradecane were weighed into a reaction bottle, and then 20 mL of tap water, 0.05 mmol of 4-dimethylaminopyridine and a magnet were added respectively. Subsequently, the reaction system was stirred at 85°C for 7 h, the reaction was stopped, and a white solid intermediate product (structure shown in formula (1)) was obtained by filtration.
[0130] The intermediate product was characterized by MALDI-TOF-MS. Figure 3 As shown in the figure, the peaks of the spectrum are at mass-to-charge ratios of 1369.350, 1581.509, 1793.666, 2005.817, 2217.964, 2430.107, and 2642.248, which correspond to the molecular ion peaks of alkyl-modified β-cyclodextrin (Formula 1) obtained by ring-opening reaction of 1 to 7 primary hydroxyl groups with 1,2-epoxytetradecane. This result proves that the hydrophobic alkyl chain was successfully grafted onto the cyclodextrin skeleton to obtain the reaction intermediate. At the same time, Figure 3 From the intensity of MALDI-TOF-MS, it can be seen that in the product of the structure shown in formula (1), x is 2 and y+z=5.
[0131] Add 1g of the intermediate product and 10mL of N,N-dimethylformamide into a three-necked flask. At the same time, weigh 2g of sulfur trioxide pyridine complex (active SO 3 The cyclodextrin-based surfactant (containing 50 wt %) was dissolved in 5 mL of N,N-dimethylformamide, added into a three-necked flask containing the intermediate product, stirred at 50 ° C for 2 h, cooled to room temperature, and a 10 wt % sodium hydroxide aqueous solution was added to adjust the pH value to 7. The solvent was removed by rotary evaporation and dried to obtain the product cyclodextrin-based surfactant (structure as shown in formula (2)), with a yield of 81%.
[0132] The product cyclodextrin-based surfactant is 1 H NMR characterization (the deuterated solvent used was deuterated water), the results are as follows Figure 4 As shown, 1 H NMR (D 2 O):δ=0.78(-C 11 H 22 CH 3 ),1.20-1.65(-C 11 H 22 CH 3 ),3.28-3.85(-CH 2 OH,-CH-CH 2 -O-CH 2 -CHOH-C 12 H 25 ,-O-CH-CH-CH 2 -O-,-CHOH,),4.06(-CH-CH 2 -OSO 3 Na), 4.18-4.49(-CH-CH 2 -OSO 3 Na,-CH-CH 2 -O-CH 2 -CHOH-C 12 H 25 ).
[0133] Depend on Figure 4 It can be seen that there are two broad peaks at 4.06 and 4.18-4.49 ppm. Among them, 4.06 ppm corresponds to -CH-CH 2 OSO 3 Na, 4.18-4.49 ppm corresponds to -CH-CH 2 -OSO 3 Na and -CH-CH 2 -O-CH 2 -CHOH-C 12 H 25, proving the successful progress of the sulfonation reaction and the existence of the sulfonation product.
[0134] The average sulfonation degree of the cyclodextrin-based surfactant in this embodiment is 1.15 mmol / g, and the sulfonation degree is determined by titration with a NaOH standard solution according to the literature (China Paper Industry, 2006, (11): 38-40).
[0135] Example 1
[0136] Weigh 2 g of cyclodextrin-based surfactant, 40 mL of 500 mg / L modified graphene oxide aqueous dispersion, and 960 mL of formation water (mineralization 20000 mg / L) into a beaker, and stir at 500 rpm for 30 min at 25°C until the mixture is uniformly mixed to obtain composite viscosity reducer A1;
[0137] In the composite viscosity reducer, the mass concentration of modified graphene oxide is 20 mg / L, and the mass concentration of cyclodextrin-based surfactant is 2000 mg / L.
[0138] Example 2
[0139] Weigh 3 g of cyclodextrin-based surfactant, 20 mL of 500 mg / L modified graphene oxide aqueous dispersion, and 980 mL of formation water (mineralization 20000 mg / L) into a beaker, and stir at 200 rpm for 40 min at 35 °C until the mixture is uniformly mixed, thereby obtaining composite viscosity reducer A2;
[0140] In the composite viscosity reducer, the mass concentration of modified graphene oxide is 10 mg / L, and the mass concentration of cyclodextrin-based surfactant is 3000 mg / L.
[0141] Example 3
[0142] Weigh 1 g of cyclodextrin-based surfactant, 100 mL of 500 mg / L modified graphene oxide aqueous dispersion, and 900 mL of formation water (mineralization 20000 mg / L) into a beaker, and stir at 100 rpm for 60 min at 25 °C until the mixture is uniformly mixed, thereby obtaining composite viscosity reducer A3;
[0143] In the composite viscosity reducer, the mass concentration of modified graphene oxide is 50 mg / L, and the mass concentration of cyclodextrin-based surfactant is 1000 mg / L.
[0144] Example 4
[0145] Weigh 0.5 g of cyclodextrin-based surfactant, 60 mL of 500 mg / L modified graphene oxide aqueous dispersion, and 940 mL of formation water (mineralization 20000 mg / L) into a beaker, and stir at 500 rpm for 60 min at 10° C. until the mixture is uniformly mixed, thereby obtaining composite viscosity reducer A4;
[0146] In the composite viscosity reducer, the mass concentration of modified graphene oxide is 30 mg / L, and the mass concentration of cyclodextrin-based surfactant is 500 mg / L.
[0147] Example 5
[0148] Weigh 5 g of cyclodextrin-based surfactant, 20 mL of 500 mg / L modified graphene oxide aqueous dispersion, and 980 mL of formation water (mineralization 20000 mg / L) into a beaker, and stir at 500 rpm for 40 min at 25°C until the mixture is uniformly mixed to obtain composite viscosity reducer A5;
[0149] In the composite viscosity reducer, the mass concentration of modified graphene oxide is 10 mg / L, and the mass concentration of cyclodextrin-based surfactant is 5000 mg / L.
[0150] Example 6
[0151] Weigh 0.8 g of cyclodextrin-based surfactant, 30 mL of 500 mg / L modified graphene oxide aqueous dispersion, and 970 mL of formation water (mineralization 20000 mg / L) into a beaker, and stir at 350 rpm for 50 min at 25° C. until the mixture is uniformly mixed, thereby obtaining composite viscosity reducer A6;
[0152] In the composite viscosity reducer, the mass concentration of modified graphene oxide is 15 mg / L, and the mass concentration of cyclodextrin-based surfactant is 800 mg / L.
[0153] Comparative Example 1
[0154] In this comparative example, composite viscosity reducer DA1 was prepared according to the method of Example 1, except that modified graphene oxide aqueous dispersion was not added in this comparative example.
[0155] Comparative Example 2
[0156] In this comparative example, composite viscosity reducer DA2 was prepared according to the method of Example 1, except that 40 mL of 500 mg / L modified graphene oxide aqueous dispersion was replaced with 40 mL of 500 mg / L unmodified graphene oxide aqueous dispersion (i.e., graphene oxide aqueous dispersion).
[0157] Comparative Example 3
[0158] In this comparative example, composite viscosity reducer DA3 was prepared according to the method of Example 1, except that the mass of cyclodextrin-based surfactant was replaced by β-cyclodextrin.
[0159] Comparative Example 4
[0160] In this comparative example, modified graphene oxide aqueous dispersion H1 was prepared according to the method for preparing modified graphene oxide nanosheet dispersion in Example 1 of CN114058342A;
[0161] Then, a composite viscosity reducer DA4 was prepared according to the method of Example 1 of the present invention, except that 500 mg / L of modified graphene oxide aqueous dispersion was replaced by 500 mg / L of modified graphene oxide aqueous dispersion H1.
[0162] Comparative Example 5
[0163] In this comparative example, modified graphene oxide nanomaterials were prepared according to the method of Preparation Example 1, except that 1.5 g of polyethylene glycol monoglycidyl ether in Preparation Example 1 was replaced with 1.5 g of polyethylene glycol diglycidyl ether to obtain modified graphene oxide aqueous dispersion H2;
[0164] Then, a composite viscosity reducer DA5 was prepared according to the method of Example 1 of the present invention, except that 500 mg / L modified graphene oxide aqueous dispersion was replaced by 500 mg / L modified graphene oxide aqueous dispersion H2.
[0165] Test Example 1: Salt resistance test
[0166] 100 mL of each composite viscosity reducer obtained in the above examples and comparative examples was placed in a glass test tube, then allowed to stand for 30 minutes and the state of the system was observed. The results are shown in Table 1 below:
[0167] Table 1 State of composite viscosity reducer
[0168] Examples state Example 1 Homogeneous clear solution Example 2 Homogeneous clear solution Example 3 Homogeneous clear solution Example 4 Homogeneous clear solution Example 5 Homogeneous clear solution Example 6 Homogeneous clear solution Comparative Example 1 Homogeneous clear solution Comparative Example 2 Flocculent precipitate Comparative Example 3 Homogeneous clear solution Comparative Example 4 Flocculent precipitate Comparative Example 5 Flocculent precipitate
[0169] As shown in Table 1, the modified graphene oxide materials used in Examples 1-6 have good salt tolerance, and the viscosity reducers prepared with formation water are all clear solutions. Comparative Example 2 has flocculent precipitation, indicating that the unmodified graphene oxide has poor salt tolerance. Even when a cyclodextrin-based surfactant is added as a stabilizer, it is still observed to be precipitated into a black flocculent. In addition, Comparative Example 3 shows that both cyclodextrin-based surfactants and cyclodextrin can stabilize the modified graphene oxide and inhibit its precipitation in saline formation water.
[0170] The composite viscosity reducer of Comparative Example 4 has flocculent precipitation, which indicates that the entanglement between the dodecyl tail chains on the surface of the modified graphene nanomaterial described in CN114058342A plays a bridging role, making the nanomaterial easy to agglomerate in salt water, and the addition of cyclodextrin-based surfactants cannot prevent the precipitation of the material. The situation of Comparative Example 5 is similar to that of Comparative Example 4. Polyethylene glycol diglycidyl ether contains an epoxy three-membered ring reaction site at each end, so it can bridge multiple nanosheets together, making the material easy to precipitate, and is not suitable for saline formation water systems.
[0171] Test Example 2: Surface activity test
[0172] The surface tension values of the composite viscosity reducers prepared in the examples and comparative examples were measured using a K100 surface tension meter from KRUSS, Germany, using a hanging plate method. The test temperature was 25° C. The test results are shown in Table 2. For the viscosity reducers with precipitated precipitation, the precipitate was filtered and then the surface tension of the clarified aqueous solution was tested.
[0173] Table 2 Surface tension of composite viscosity reducer in each embodiment and comparative example
[0174] Examples Surface tension / (mPa·s) Example 1 32.1 Example 2 32.8 Example 3 33.3 Example 4 33.7 Example 5 32.6 Example 6 34.0 Comparative Example 1 35.5 Comparative Example 2 36.0 Comparative Example 3 59.8 Comparative Example 4 34.6 Comparative Example 5 35.8
[0175] As can be seen from the above table, the surface tension of the composite viscosity reducer in Examples 1-6 is at least 1.5 mN / m lower than that of a single cyclodextrin-based surfactant (Comparative Example 1), because the two components of the composite system form an active composite. At the same time, Comparative Example 3 shows that even if unmodified cyclodextrin and modified graphene oxide form a composite, their interfacial activity is poor. The results of Comparative Example 4 show that after the modified graphene oxide nanomaterial is precipitated, some of the free N-(2-hydroxyethyl) dodecylamide molecules act together with the cyclodextrin-based surfactant at the water-gas interface, which can reduce the surface tension to 34.6 mN / m. In Comparative Examples 2 and 5, after the modified nanomaterial is precipitated, the residue in the aqueous solution is a cyclodextrin-based surfactant, and its surface tension is close to that of Comparative Example 1.
[0176] Test Example 3: Viscosity reduction performance test
[0177] The composite viscosity reducers in the examples and comparative examples were used to measure the viscosity reduction rate of heavy oil. The test oil was taken from the heavy oil in Chenzhuang block of Shengli Oilfield, and its viscosity at 50°C was 13370 mPa·s, which was an extra-heavy oil.
[0178] The specific test steps for heavy oil viscosity reduction are as follows:
[0179] (a) Take 20 g of heavy oil sample and place it in a distillation flask;
[0180] (b) adding 10 grams of the composite viscosity reducer in the example to the distillation flask;
[0181] (c) allowing the mixture to react at 50° C. for 2 hours and then gently shaking to obtain an oil-water mixed emulsion, and then measuring its viscosity at 50° C. using a Haake VT550 rotational viscometer;
[0182] (d) Calculate the viscosity reduction rate of heavy oil by the following formula: M = [(η 1 -η 2 ) / η 1 ]×100%,
[0183] Where η 1 Refers to the viscosity of crude oil (mPa·s); η 2 It refers to the viscosity of crude oil emulsion (mPa·s);
[0184] M is the viscosity reduction rate.
[0185] The viscosity reduction results of the composite viscosity reducers obtained in the examples and comparative examples are shown in Table 3. For the viscosity reducers with precipitated precipitation, the precipitate was filtered and then tested using a clarified aqueous solution.
[0186] Table 3 Viscosity reduction rate of composite viscosity reducer in each embodiment and comparative example
[0187] System viscosity after adding viscosity reducer / (mPa·s) Viscosity reduction rate / % Example 1 42 99.7 Example 2 57 99.6 Example 3 66 99.5 Example 4 103 99.2 Example 5 56 99.6 Example 6 132 99.0 Comparative Example 1 2105 84.3 Comparative Example 2 2886 78.4 Comparative Example 3 12243 8.4 Comparative Example 4 1008 92.5 Comparative Example 5 2337 82.5
[0188] In the results of Table 3, the viscosity reducers used in Examples 1-6 can form water-in-oil emulsions with heavy oil, and the viscosity reduction rate is higher than 99%. This is because the cyclodextrin-based surfactant forms a complex with the modified graphene oxide, which brings two effects: on the one hand, the complex is enriched at the interface to form an oil-water interface film with both rigidity and flexibility, which has an excellent emulsification effect; on the other hand, the modified graphene oxide in the complex can attract the amphiphilic colloid of the heavy oil to enrich at the interface through the π-π action, and finally show a higher viscosity reduction rate.
[0189] Comparative Example 1 shows that, without the addition of modified graphene oxide, the viscosity reduction rate of the cyclodextrin-based surfactant itself on the heavy oil is relatively low, at 84.3%. This shows that the stabilizing effect of modified graphene oxide on the interface plays a key role in achieving ultra-high viscosity reduction. In Comparative Examples 2 and 5, the nanomaterials are precipitated, and the viscosity reduction performance of the system is similar to that of Comparative Example 1. In Comparative Example 3, the interfacial activity of the mixed system of β-cyclodextrin and modified graphene oxide is poor, and its viscosity reduction rate is only 8.4%. In Comparative Example 4, after the nanomaterials are precipitated, some free N-(2-hydroxyethyl) dodecylamide molecules act together with the cyclodextrin-based surfactant at the oil-water interface, and the viscosity reduction rate is 92.5%.
[0190] Test Example 4: Determination of the adsorption properties of modified graphene oxide on rock surfaces
[0191] According to the literature method (Rui Liu, Shi Gao, Qin Peng, et al. Experimental and molecular dynamic studies of amphiphilic graphene oxide for promising nanofluid flooding, Fuel, 2022, 330, 125567), the adsorption properties of modified graphene oxide nanomaterials on the rock surface were measured. Figure 5 The UV-visible spectrum of the modified graphene oxide aqueous dispersion obtained in Preparation Example 1 has a highest peak at 231 nm. By changing the mass concentration of modified graphene oxide (1 mg / L, 2 mg / L, 6 mg / L, 10 mg / L), the ultraviolet absorbance of the system at 231 nm was measured to make a standard curve of mass concentration and absorbance of modified graphene oxide.
[0192] 15g of heavy oil from the Chenzhuang block of Shengli Oilfield was taken and dispersed evenly with 85g of petroleum ether at 60°C to obtain a heavy oil dispersion. Then, an artificial sandstone slice with a diameter of 2.5cm, a height of 0.1cm, and a thickness of 1cm was placed in the heavy oil dispersion and immersed for 24h, taken out and dried to constant weight to obtain an oil-wet surface rock slice.
[0193] The untreated rock slice and the oil-wet rock slice were immersed in 30 mL of the composite viscosity reducer prepared in Example for 4 hours respectively, the upper liquid was taken to measure its ultraviolet absorption curve, and then the concentration of modified graphene oxide in the upper liquid was obtained according to the standard curve. The measurement results are shown in Table 4.
[0194] Table 4 Adsorption amount of modified graphene oxide on rock surface in each embodiment and comparative example
[0195]
[0196] As shown in Table 4, the amount of modified graphene oxide contained in the composite viscosity reducer prepared in Examples 1-6 on the surface of untreated rock slices is small, and the concentration of modified graphene oxide in the aqueous phase does not change much. However, the amount of modified graphene oxide nanomaterials adsorbed on the surface of oil-wet rock slices is large, and the residual concentration in the dispersion after adsorption is very low. This result shows that under the entrapment of cyclodextrin-based surfactants, the modified graphene oxide nanomaterials contained in the composite viscosity reducers in Examples 1-6 can be targeted and released on the oil-containing surface, and there is little loss on the surface of oil-free rock. This targeted release performance is conducive to improving the efficiency of modified graphene oxide and reducing the cost of material application.
[0197] The composite viscosity reducers prepared in Comparative Examples 2, 4 and 5 cannot prove their targeted release effect due to the precipitation of graphene oxide nanomaterials. The results of Comparative Example 3 show that β-cyclodextrin itself can also make the nanomaterial have a certain targeted release effect when encountering oil, but the adsorption loss of the nanomaterial on the surface of the untreated rock slice is higher than that in Example 1, which shows that the cyclodextrin-based surfactant selected in the example can make the modified graphene oxide nanomaterial have a better targeted release effect.
[0198] Test Example 5: CO 2 Responsive demulsification test
[0199] The oil-water emulsions formed in Examples 1-3 and Comparative Example 4 in Test Example 3 were selected, and CO was introduced into the oil-water mixed emulsion at a gas flow rate of 1 L / min. 2 After 3 minutes of ventilation, let it stand and record the time required for emulsion demulsification. 2 The time required for emulsion demulsification is shown in Table 5:
[0200] Table 5 Time required for emulsion demulsification in each embodiment and comparative example
[0201] <![CDATA[Introduce CO 2 The time required for demulsification after <![CDATA[Do not introduce CO 2 Demulsification time required]]> Example 1 15.2min 28.5h Example 2 13.3min 18.6h Example 3 15.5min 29.5h Example 4 14.8min 28.0h Example 5 12.5min 18.0h Example 6 13.5min 19.0h Comparative Example 1 2.0h 1.2h Comparative Example 2 2.0h 1.0h Comparative Example 3 -(Not emulsified) -(Not emulsified) Comparative Example 4 72.0h 96.0h Comparative Example 5 2.0h 1.0h
[0202] It can be seen that in Examples 1-6, when CO is introduced 2 After that, the system demulsifies very quickly, and the time required for emulsion demulsification does not exceed 20 minutes. 2 In all cases, the demulsification time exceeded 18 hours.
[0203] Comparative Example 1 does not contain modified graphene oxide. 2 The time required for emulsion demulsification before and after is not much different, both within the range of 1.0-2.0h; since the nanomaterials are precipitated in the brine, the emulsion demulsification performance of Comparative Examples 2 and 5 is similar to that of Comparative Example 1. The viscosity reduction rate of the composite viscosity reducer used in Comparative Example 3 is very low, and the heavy oil is basically not emulsified, so the demulsification time cannot be measured. However, since Comparative Example 4 contains free unreacted single-chain small molecule surfactants, the demulsification time of its produced fluid is as long as 96h. After the introduction of carbon dioxide, the small molecule surfactants are still enriched at the oil-water interface, and the demulsification time is still as long as 72h.
[0204] In summary, the modified graphene oxide nanomaterial contained in the composite viscosity reducer of the present invention has the effect of targeted release when encountering oil, can effectively emulsify the heavy oil, achieve efficient viscosity reduction, and can reduce the adsorption loss of the material; at the same time, the mixed emulsion formed by the viscosity reducer and the heavy oil has CO 2 The characteristic of responsive demulsification makes the post-treatment of heavy oil produced fluid simple, overcomes the technical difficulty of demulsification of nano-viscosity reduction system, and has good practical application value.
[0205] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composite viscosity reducer, characterized in that: The composite viscosity reducing agent contains the following components which are stored independently or in a mixture of two or more: a cyclodextrin-based surfactant, water and modified graphene oxide; The modified graphene oxide comprises graphene oxide and grafted polyethylene oxide chains, wherein the chemical formula of the polyethylene oxide chain is -CH2CH(OH)CH2O(CH2CH2O) n CH2CH2OH, wherein n is selected from any integer from 3 to 20; The cyclodextrin-based surfactant contains -OSO3Na groups and -OH groups; The mass ratio of the modified graphene oxide to the cyclodextrin-based surfactant is 1:(10-500).
2. The composite viscosity reducer according to claim 1, wherein: The grafting rate of the polyoxyethylene chains in the modified graphene oxide is 30-50%, preferably 35-46%; Preferably, n in the polyoxyethylene chain is any integer from 5 to 15; Preferably, the mass ratio of the modified graphene oxide to the cyclodextrin-based surfactant is 1:(15-200).
3. The composite viscosity reducer according to claim 1 or 2, wherein: The modified graphene oxide is added in the form of a modified graphene oxide aqueous dispersion; Preferably, the modified graphene oxide aqueous dispersion is prepared by a method comprising the following steps: S1: Under alkaline conditions, the graphene oxide aqueous dispersion is activated with β-cyclodextrin to obtain an activation solution; S2: performing a grafting reaction on the activation solution and polyethylene glycol monoglycidyl ether to obtain a grafted product; S3: using an acid to adjust the pH value of the grafted product to neutral, and then adding amylase to wash it to obtain the modified graphene oxide aqueous dispersion.
4. The composite viscosity reducer according to claim 3, wherein: In step S1, the conditions of the activation reaction include: reaction temperature of 60-100°C, preferably 70-90°C; reaction time of 1-4h, preferably 2-3h; Preferably, in step S2, the grafting reaction conditions include: reaction temperature of 60-100°C, preferably 70-90°C; reaction time of 4-16h, preferably 6-12h; Preferably, in step S3, the washing time is 1-4 hours, preferably 2-3 hours.
5. The composite viscosity reducer according to claim 3 or 4, wherein: In step S1, the concentration of graphene oxide in the graphene oxide aqueous dispersion is greater than 20 mg / L, preferably 500-2000 mg / L; Preferably, based on the total volume of the mixed solution of graphene oxide aqueous dispersion and cyclodextrin as 1L, the amount of β-cyclodextrin used is 100-800 mg, preferably 300-500 mg; Preferably, the mass ratio of polyethylene glycol monoglycidyl ether to graphene oxide is (5-100):1, preferably (10-30):1; Preferably, in step S3, based on the total volume of the graphene oxide aqueous dispersion as 1 L, the amount of the amylase used is 50-800 mg, preferably 100-400 mg.
6. The composite viscosity reducer according to any one of claims 3 to 5, wherein: In step S2, the polyethylene glycol monoglycidyl ether is prepared by the following method: Carrying out a first reaction between polyethylene glycol, potassium carbonate and epichlorohydrin under stirring conditions to obtain the polyethylene glycol monoglycidyl ether; The molar ratio of the polyethylene glycol, potassium carbonate and epichlorohydrin is 1:(0.1-1):(1.1-10), preferably 1:(0.5-1):(1.5-10); Preferably, the temperature of the first reaction is 20-50°C, preferably 25-40°C; the reaction time is 12-36h, preferably 20-30h.
7. The composite viscosity reducer according to any one of claims 1 to 6, wherein: The cyclodextrin-based surfactant has a structure shown in formula (I): Wherein, in the structure of formula (I), x is 2, y is any integer selected from 1-5, z is any integer from 0-4, and y+z=5, -C 12 H 25 represents n-dodecyl.
8. The composite viscosity reducer according to any one of claims 1 to 7, wherein: The amount of water used is such that in the composite viscosity reducer, the mass concentration of the modified graphene oxide is 10 mg / L-50 mg / L, and the mass concentration of the cyclodextrin-based surfactant is 500 mg / L-5000 mg / L; Preferably, the amount of water used is such that in the composite viscosity reducer, the mass concentration of the modified graphene oxide is 10 mg / L-30 mg / L, and the mass concentration of the cyclodextrin-based surfactant is 1000 mg / L-2000 mg / L.
9. A method for preparing the composite viscosity reducer according to any one of claims 1 to 8, characterized in that: The method comprises: contacting a cyclodextrin-based surfactant, modified graphene oxide and water; Preferably, the contacting conditions include: temperature of 10-35°C, time of 30-60 min, and stirring speed of 100-500 rpm.
10. Use of the composite viscosity reducer according to any one of claims 1 to 8 in the field of heavy oil production.
11. A method for responsive demulsification of heavy oil produced fluid, characterized in that: The method includes: (1) bringing the composite viscosity reducer according to any one of claims 1 to 8 into first contact with heavy oil to obtain an oil-water mixed emulsion; (2) CO2 is introduced into the oil-water mixed emulsion to cause the oil-water mixed emulsion to responsively break up the emulsion and separate water.
12. The method according to claim 11, wherein: In step (1), the mass ratio of the composite viscosity reducer to the heavy oil is 3:7 to 7:
3.
13. The method according to claim 11 or 12, wherein: In step (1), the conditions for the first contact include: temperature of 40-60° C. and time of 10-300 min.
14. The method according to any one of claims 11 to 13, wherein: In step (2), the CO2 gas flow rate is 0.5-5 L / min, and the ventilation time is 1-5 min; Preferably, in step (2), the CO2 gas flow rate is 0.5-2 L / min, and the ventilation time is 1-5 min.
Citation Information
Patent Citations
Demulsification method of oil-in-water type crude oil emulsion
CN104877706A
Sterilizing cleaning composition with rich and stable foam
CN105331447A
Thickened oil viscosity reducer and using method thereof
CN111394080A
Functionalized graphene oxide nitrile rubber and tooth-scar-free tooth block
US20230002593A1